Driver Drowsiness Warning System Using Visual Information for Both Diurnal and Nocturnal Illumination Conditions. (11th July 2010) - Flores Flores, Marco Javier Marco Javier; Armingol Armingol, José María José María; de la Escalera de la Escalera, Arturo Arturo
Abstract : Every year, traffic accidents due to human errors cause increasing amounts of deaths and injuries globally. To help reduce the amount of fatalities, in the paper presented here, a new module for Advanced Driver Assistance System (ADAS) which deals with automatic driver drowsiness detection based on visual information and Artificial Intelligence is presented. The aim of this system is to locate, track, and analyze both the drivers face and eyes to compute a drowsiness index, where this real-time system works under varying light conditions (diurnal and nocturnal driving). Examples of different images of drivers taken in a real vehicle are shown to validate the algorithms used.